Strategi Komunikasi Pemasaran Pada UMKM Magetan Bamboo Craft di Kabupaten Magetan dalam Mengembangkan Usahanya - Widya Yusti Atlisiaji (CV. Adiguna Kertosari, 2021)
Magetan Regency is the second smallest Regency in East Java after Sidoarjo with a location at the westernmost tip of East Java, making this regency rarely visited by tourists. In Magetan Regency, there is a lot of potential that can be developed, one of which is in the field of developing Micro, Small and Medium Enterprises (MSMEs), namely Magetan Bamboo Craft. This article aims to increase sales, expand the market share of the creative business of craft home industry in Magetan Regency where often at exhibitions abroad or at the national level there is a good response, but on the way there are still many who do not know about sponge products. this. One of the integrated marketing strategies is to introduce products to the public or the public. The use of brochures, leaflets, leaflets and the use of internet technology is often an option for MSME actors because they are considered efficient without having to spend a lot of money. So far, the marketing of Magetan Bamboo Craft is only limited to orders from consumers, co-workers, guests from the district, individuals and families as well as friends who are known by the owner of the craft business. The marketing communication strategies carried out in this study include providing training in the creation of content and brochures, as well as the use of internet usage such as the use of social media Instagram, WhatsApp and Facebook as well as websites as an effort to maximize the means of disseminating information and product marketing. In addition, the provision of socialization is useful as an understanding for SMEs owners of Sponge Bread in order to understand the concept of integrated communication marketing and its application. If these two things (training on making brochures and blogs as well as socialization) have been carried out, then the author just needs to provide assistance and open a consultation session regarding the development and changes in marketing attitudes in the future. To obtain data, this research uses the deep interview method or in-depth interviews with the MSME Cooperative Office of Magetan Regency.